Long-term outcomes over 10 years after femoral derotation osteotomy in ambulatory children with cerebral palsy - Sung, Ki Hyuk; Kwon, Soon Sun; Chung, Chin Youb; Lee, Kyoung Min; Cho, Gyeong Hee; Park, Moon Seok (Gait and Posture, 2018)
Background: Femoral derotation osteotomy (FDO) is generally reported to be excellent for correcting the hip rotation and foot progression angles in children with cerebral palsy (CP). However, it is unclear how long the favorable outcomes are maintained. Research question: This study was performed to evaluate the long-term outcomes at more than 10 years after FDO in children with CP. Methods: FDO, as part of single event multilevel surgery to improve gait function, was performed at the intertrochanteric level with the patient in the prone position. The goal of the index surgery was femoral anteversion of 15° measured using a modified trochanteric prominence angle test intraoperatively. All patients underwent three-dimensional gait analysis preoperatively and at 1 year and over 10 years postoperatively. Results: Thirty-four ambulatory patients (53 hips) with CP undergoing FDO were included. The mean age at surgery was 7.8 years (SD = 3.0 years) and mean follow-up duration was 12.9 years (SD = 2.7 years). The mean hip rotation decreased significantly from 9.6° preoperatively to 3.1° at 1 year postoperatively (p = 0.004), and decreased significantly to -5.9° at the final follow-up (p < 0.001). The mean foot progression in stance decreased from 7.9° preoperatively to −7.4° at 1 year postoperatively (p < 0.001), and was maintained at -10.9° at the final follow-up. The GDI significantly improved from 68.2 preoperatively to 83.4 1 year postoperatively (p < 0.001), and was maintained at 82.3 at the final follow-up. No patients underwent revision surgery due to recurrence of rotation deformity. Significance: Proximal FDO performed in the prone position provides favorable long-term outcomes at more than 10 years postoperatively, without recurrence of rotation deformity. To avoid under-correction or recurrence due to insufficient derotation, surgeons should consider not only dynamic gait analysis findings but also the measurement of anatomic femoral anteversion during intraoperative derotation.
Keywords: Adolescent; Cerebral Palsy; Child; Child, Preschool; Female; Femur; Follow-Up Studies; Foot; Gait; Gait Disorders, Neurologic; Hip Joint; Humans; Male; Osteotomy; Postoperative Period; Range of Motion, Articular; Retrospective Studies; Treatment Outcome; Anteversion; Cerebral palsy; Femoral derotation osteotomy; Gait analysis